Association of single nucleotide polymorphism in the loxl1 gene with pseudoexfoliation syndrome in northwestern Rajasthan - Parul Bansal, Dr.; Twinkle Garg, Dr.; Jaishri Murli Manoher, Dr.; Anil Chouhan, Dr. (International Journal of Biological Research, 2024)
Purpose: To identify, evaluate and establish the relation of LOXL1 gene polymorphism among patients with pseudoexfoliation syndrome in North West Rajasthan. Methods: 50 patients diagnosed with pseudoexfoliation syndrome and 50 healthy subjects of age >40 years were enrolled in the study. All participants underwent routine ophthalmic examination. 2ml blood samples were taken of each participant which were sent to Multi Disciplinary Research Unit to be checked for specific gene mutation using Polymerase Chain Reaction technique. Results and conclusion: Study showed that rs10486(G) SNP and rs21652(T) SNP has been present in general population also but is more prevalent in those with pseudoexfoliation syndrome. While, rs38259(G) SNP was found not to be a significant factor in development of pseudoexfoliation syndrome. Understanding the genetic basis of pseudoexfoliation syndrome would further contribute in aiding the early diagnosis and management of this disease.